1997
DOI: 10.1111/j.2044-8325.1997.tb00633.x
|View full text |Cite
|
Sign up to set email alerts
|

PMS in the workplace: Dispelling the myth of cyclic dysfunction

Abstract: To examine the notion that cyclic dysfunction among female employees is a pervasive workplace problem, 438 employees completed a survey of the past week's stress, health and work experiences. A 4 (menstrual cycle status) X 2 (occupational level) analysis showed no differences between groups of perimenstrual women, postmenstrual women, non-menstruating women, and male colleagues on dimensions of illness, wellness, work performance, absenteeism, or subjective stress; although there were occupational differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…To date, research has primarily focused on the relationship between premenstrual symptom severity and the rates of absenteeism, job performance and productivity. Several studies have shown reductions in work productivity, performance, and higher absence from work in staff who reported problematic premenstrual symptoms (e.g., [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]), with very few exceptions (e.g., [ 21 ]). Borenstein and colleagues [ 13 ] found a 13.7% absenteeism rate (days taken as absence) for women with premenstrual symptoms and a 15% reduction in work productivity ( N = 364).…”
Section: Introductionmentioning
confidence: 99%
“…To date, research has primarily focused on the relationship between premenstrual symptom severity and the rates of absenteeism, job performance and productivity. Several studies have shown reductions in work productivity, performance, and higher absence from work in staff who reported problematic premenstrual symptoms (e.g., [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]), with very few exceptions (e.g., [ 21 ]). Borenstein and colleagues [ 13 ] found a 13.7% absenteeism rate (days taken as absence) for women with premenstrual symptoms and a 15% reduction in work productivity ( N = 364).…”
Section: Introductionmentioning
confidence: 99%
“…[4] There is also some debate as to whether PMS is associated with the performance of women in the workplace. [5,6] Although PMS is very common, Houston et al [7] indicated that only 2% of teenage women reported receiving information regarding menstruation from their healthcare providers. In some conservative areas, such as Asian countries, menstruation and its related problems are considered to be taboo topics.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…Although research to fill the numerous gaps in our understanding of PMS is encouraged, methodologic imprecision compromises Hardie's findings. Hardie (1997), in an article titled "PMS in the Workplace: Dispelling the Myth of Cyclic Dysfunction," claimed to provide evidence that menstrual cycle status has no effect on female employees' work performance. In doing so, she opened and closed her presentation by referencing our earlier work, published in this journal, in which we (Phillips & Bedeian, 1989) offered that there was yet clear-cut scientific evidence that premenstrual syndrome (PMS) adversely affects workplace behavior.…”
mentioning
confidence: 96%
“…
Hardie (1997) purportedly examined the effects of menstrual cycle status and perceived (i.e., self-diagnosed) premenstrual syndrome on work performance. Although research to fill the numerous gaps in our understanding of PMS is encouraged, methodologic imprecision compromises Hardie's findings.
…”
mentioning
confidence: 99%